2017
DOI: 10.1002/ceat.201600475
|View full text |Cite
|
Sign up to set email alerts
|

Rheological, Thermodynamic, and Gas Solubility Properties of Phenylacetic Acid‐Based Deep Eutectic Solvents

Abstract: Choline chloride + phenylacetic acid-based deep eutectic solvents are studied. Their most relevant experimental physicochemical properties at different mixing ratios together with the CO 2 solubility data obtained in wide pressure and temperature ranges are reported. The presented materials exhibit a significant CO 2 capture performance with low corrosion effect when compared with the most common amine-based CO 2 capture agents. Detailed rheological measurements are carried out and various models are applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 48 publications
(50 reference statements)
1
19
1
Order By: Relevance
“…Linear behavior of the density values are assured with the experimental temperature variation. Moreover, in Figure , density trends obtained from previous study for DES systems obtained by mixing same HBD, [ChCl], with non‐natural organic acids, levulinic acid ([LAA]) and phenyl acetic acid ([PAA]) compared with the NADES systems studied in this work. It has been observed that the density values obtained from the natural HBD to form NADES systems have caused higher density values.…”
Section: Resultscontrasting
confidence: 72%
See 1 more Smart Citation
“…Linear behavior of the density values are assured with the experimental temperature variation. Moreover, in Figure , density trends obtained from previous study for DES systems obtained by mixing same HBD, [ChCl], with non‐natural organic acids, levulinic acid ([LAA]) and phenyl acetic acid ([PAA]) compared with the NADES systems studied in this work. It has been observed that the density values obtained from the natural HBD to form NADES systems have caused higher density values.…”
Section: Resultscontrasting
confidence: 72%
“…It has been observed that the density values obtained from the natural HBD to form NADES systems have caused higher density values. In [ChCl]:[PAA] system the water content was reported as ∼0.8 % and for [ChCl]:[LAA] system the water content was previously reported as ∼1.69 %, which are lower than that of the water content values reported for the studied NADES systems in this work.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the yield stresses of all NADESs decreased with increasing temperature as expected for the shear thinning materials. The differences in the yield stress values are mainly due to the changes in the interaction forces between the hydrogen bond donor and hydrogen accepter of the NADES and the molecular weight [44,46]. The variations of the yield stress values as a function of temperature is similar to the viscosity data (see Fig.…”
Section: Nades Systemssupporting
confidence: 68%
“…Moreover, further calibration was conducted by using dimethyl sulfoxide (DMSO) at various isotherms and experimental results were compared with literature values. Further details on the calibration of the vibrating tube apparatus can be obtained elsewhere [46]. The uncertainty temperature and the pressure measurements in densitometer is ±0.05 K and 0.005 MPa.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation